Taste Memory: Food Serving Traditions In The Khol Agung Celebration Based On Serat Memulé At Mangkunegaran Palace In 1916-1944m: Memori Cita Rasa: Tradisi Penyajian Makanan Dalam Perayaan Khol Agung Berdasarkan Serat Memulé Di Pura Mangkunegaran Tahun 1916-1944m - Nur Fadlilah; Sucipto; Muh. Fajar Shodiq; Latif Kusairi (Al-Absah: Journal of Civilization, Language, Literature, and History, 2025)
This study discusses the history of the tradition of serving food in the khol agung celebration at Pura Mangkunegaran in the period 1916–1944, based on the Serat Memulé manuscript. The tradition of serving food in khol agung is an important part of the ritual to commemorate the death of the Mangkunegaran king, which is held once every eight years. The purpose of this study is to trace the early history of the tradition of serving food in the khol agung celebration at Pura Mangkunegaran. The method used is the historical method with the stages of heuristics, verification, interpretation, and historiography. A linguistic approach is also used in studying the Serat Memulé manuscript. Historical data were obtained from the Serat Memulé manuscript, Reksa Pustaka archives, contemporary newspapers, interviews and literature. The results of the study show that this tradition is rooted in the religious customs of K.G.P.A.A. Mangkunegara I and was continued by the kings after him. The progress of Javanese literature during the reign of Mangkunegara VII produced the Javanese Serat Memulé manuscript. Serat Memulé records the favorite dishes of the Mangkunegaran kings from K.G.P.A.A. Mangkunegara I to K.G.P.A.A. Mangkunegara V presented in khol agung. This tradition has spiritual meaning, religious, social, and cultural values. This tradition influences the culture of society outside the palace through similar practices known as pancenan.